International students, immigration and earnings growth: The effect of a pre-immigration host-country university education - Feng Hou; Yuqian Lu (IZA Journal of Development and Migration, 2017)
While destination-country education provides many potential advantages for immigrants, empirical studies in Australia, Canada and the USA have produced mixed results on the labour outcomes of immigrants who are former international students. This study uses large national longitudinal datasets to examine cross-cohort trends and within-cohort changes in earnings among three groups of young university graduates: immigrants who are former international students in Canada (Canadian-educated immigrants), foreign-educated immigrants who had a university degree before immigrating to Canada and the Canadian-born population. The results show that Canadian-educated immigrants on average had much lower earnings than the Canadian-born population but higher earnings than foreign-educated immigrants both in the short run and in the long run. However, Canadian-educated immigrants are a highly heterogeneous group, and the key factor differentiating their post-immigration earnings from the earnings of the Canadian-born population and foreign-educated immigrants is whether they held a well-paid job in Canada before becoming permanent residents. Furthermore, an extra year of Canadian work experience or an extra year of Canadian education experience before immigration added only a small or no earnings gain after immigration for Canadian-educated immigrants.
Keywords: J15; J24; J61; 330; International students; Immigration; Canadian education; Earnings